2018
DOI: 10.7759/cureus.2778
|View full text |Cite
|
Sign up to set email alerts
|

Fidaxomicin vs Vancomycin for the Treatment of a First Episode of Clostridium Difficile Infection: A Meta-analysis and Systematic Review

Abstract: Clostridium difficile infection (CDI) continues to possess a significant disease burden in the United States (US) as well as all over the world. Given the increase in severity and recurrence rate, the decrease in cure rate, and the fact that the virulent ribotype 027 strain remains one of the most commonly identified strains in the US, the Infectious Diseases Society of America (IDSA) published a clinical practice guideline in February 2018 moving away from metronidazole as the first-line treatment for initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
(40 reference statements)
0
15
0
4
Order By: Relevance
“…Current treatment for CDI has changed from metronidazole and vancomycin to fidaxomycin and vancomycin (14)(15)(16). Fidaxomycin carries a lower risk of recurrence, but its costeffectiveness is a topic of debate (17). The main risk factor to CDI is gut microbiota dysbiosis (12,18), associated with age and/or administration of broad-spectrum antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment for CDI has changed from metronidazole and vancomycin to fidaxomycin and vancomycin (14)(15)(16). Fidaxomycin carries a lower risk of recurrence, but its costeffectiveness is a topic of debate (17). The main risk factor to CDI is gut microbiota dysbiosis (12,18), associated with age and/or administration of broad-spectrum antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a lower incidence of CDI recurrence in fidaxomicin‐treated patients compared with those receiving vancomycin, but these studies have been mostly limited to patients with an initial episode or first recurrence 3‐10 . Furthermore, there is a paucity of data in patients with multiple prior episodes of CDI.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Fidaxomicin, in addition to being active against vegetative forms, inhibits sporulation as well and has a narrower spectrum, thus less affecting the gut microbiota. Both of these factors translate to lower recurrence rate [2,39,40], but due to high cost, fidaxomicin remains the second line of treatment in most ICUs. In patients with fulminant colitis and/or septic shock refractory to conservative treatment, colectomy is recommended [37].…”
Section: Use Of Fmt In the Intensive Care Unitmentioning
confidence: 99%